Keutamaan Bulan Ramadahan dalam Meningkatkan Iman - Aspiani, Ahmad; Kastalani, Akhmad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Ramadhan is a special moment in Islam that encompasses not only ritual aspects but also profound spiritual and social dimensions. This study aims to analyze the role of Ramadhan observances in enhancing individual faith and piety, as well as the challenges in maintaining religious consistency after the holy month. Using a descriptive qualitative approach and literature review method, this research adopts behavioral-religious theory and spiritual reinforcement as analytical frameworks. The findings reveal that Ramadhan serves as a spiritual school (madrasah ruhaniyah) that shapes character, controls desires, strengthens one’s relationship with Allah (hablum minallah), and enhances social solidarity. Despite challenges in sustaining faith post-Ramadhan, strategies such as moderate religious education, family and community support, and involvement in social activities are proven effective in maintaining religious continuity. Therefore, Ramadhan functions not only as an annual worship period but also as a sustainable medium for personal transformation among Muslims.